Girl Education: Strategies for Enhancing Girl's Education: Addressing Gender Biases Through Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Education is very important for every child whether boy or girl. It is very sad that some communities still discriminate against the education of the girl. Education is the key factor for girl's development, empowerment, prosperity and welfare. Education saves and improves the lives of girls and women. It allows women greater control of their lives and provides them with skills to contribute to their societies. It enables them to make decisions for themselves and to influence their families. There is continued inequality and vulnerability of girls in all sectors. In order to fight against the socially constructed gender biases, girls have to swim against the system that requires more strength. Such strength comes from the empowerment and empowerment will come from the education. This paper emphasis on girl's education because it enables them to responds to the challenges, to confront their traditional role and change their life. So that we can't neglect the importance of education in reference to girl's empowerment